THE FACTORS OF SERVICE, RELIGIOSITY AND KNOWLEDGE IN THE DECISION OF CUSTOMERS TO SAVE FUNDS IN SHARIA BANKS IN YOGYAKARTA CITY - Pabbajah, Mustaqim; Widyanti, Ratri Nurina; Widyatmoko, Widi Fajar (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2019)
Islamic banks are experiencing rapid development amid the current global crisis in Indonesia and even in the world. This becomes evidence that Sharia Bank can maintain its existence from all the problems of a complex economic crisis that hit in 2007. Indonesia as the largest Islamic country in the world is a potential market that supports the sustainability of Islamic banking. The Islamic sharia principles in its management, causes many people in Indonesia, especially in Yogyakarta decide to save their funds in Islamic banks. The population in this study is all Islamic bank customers in Yogyakarta, with sample selection using incidental sampling. The data analysis method used is multiple linear regression. This study shows the positive influence of service and public trust in Islamic banks. Similarly, knowledge about Islamic banks, and one's religiosity has an important role in the decision making to save funds in Islamic banks in the city. Islamic labelity and current trends supported by high community religiosity are also important factors in the decision to deposit funds in Islamic banks. In fact, the biggest influence that influences customer's decision to save funds in a bank is the quality of service and trust. Thus, the attention of banking players is needed in improving performance and banking services, so that public confidence is higher in the decision to save funds in the bank. In other words, the community remains consistent to make economic transactions with banks in order to respond to the challenges of the economic crisis in the future.